Controlled Coffee Intake Enhances Erythrocyte Deformability, Na,K-ATPase Activity, and GSH/GSSG Ratio in Healthy Young Adults - Dominika Radosinska; Tomas Jasenovec; Alzbeta Golianova; Ivan Szadvari; Rastislav Vazan; Ivona Kovacicova; Denisa Snurikova; Norbert Vrbjar; Jana Radosinska (Biomedicines)
Background: Published studies suggest that regular coffee consumption may reduce the risk of various diseases. However, many of these studies relied on questionnaire-based data, limiting their ability to identify the specific biological mechanisms behind the observed effects. This study focuses on controlled coffee consumption among healthy young adults to clarify its effects on erythrocyte properties. The functional condition of erythrocytes is important as it affects both macro- and microcirculation. Additionally, since erythrocytes are not true cells, they are particularly sensitive to biochemical and biophysical changes when exposed to biologically active substances. Methods: After a washout period, 33 healthy young volunteers were asked to consume a standardized dose of a coffee beverage daily for 3 weeks. Basic hematological and body composition parameters were recorded before and after the intervention. Erythrocyte functional status was evaluated based on the following measurements: deformability, osmotic resistance, Na,K-ATPase activity, and nitric oxide production, along with monitoring oxidative stress markers. Results: After a coffee consumption period, both erythrocyte count and hematocrit value increased, while body composition remained unchanged. Erythrocyte deformability improved across a range of shear stress values typical of human circulation. This improvement was accompanied with enhanced Na,K-ATPase activity in erythrocyte membranes in the wide range of sodium ion concentrations, as well as increased nitric oxide production by erythrocytes. Additionally, a higher GSH/GSSG ratio, indicating a shift towards a more favorable antioxidant balance, was observed in erythrocytes following the coffee intake period. Conclusions: The results of this study suggest that controlled coffee intake in healthy young adults can positively influence various indices of erythrocyte functional status. Although the observed statistically significant changes were modest, the findings consistently indicate a positive modulation of erythrocyte properties—cell deformability, oxidative resilience, and active membrane transport of cations—following coffee consumption.